Is non-vegetarian food permitted or prohibited for human being? - Naik, Zakir, 1965-; Zaveri, Rashmibhai; Indian Vegetarian Congress; Islamic Research Foundation; Rushabh Foundation; Saba Islamic Media (Kuala Lumpur : Saba Islamic Media, 2004)
This video contained a public dialogue between Zakir Naik and Rashmibhai Zaveri on Is non-vegetarian food permitted or prohibited for human being, which in 2 parts. Part 1 is a dialogue and part 2 is a question an answer session
Public dialogue between Zakir Naik and Rashmibhai Zaveri
Narrator : Zakri Naik and Rashmibhai Zaveri
Keywords: Vegetarianism -- Religious aspects -- Jainism; vegetarianism -- Religious aspects -- Islam